Identification and validation of up-regulated TNFAIP6 in osteoarthritis with type 2 diabetes mellitus - Siyi Liu; Haitao Chen; Xu Yang; Yinxian Wen; Liaobin Chen (Scientific Reports)
Abstract Lines of evidence have indicated that type 2 diabetes mellitus (T2DM) is an independent risk factor for osteoarthritis (OA) progression. However, the study focused on the relationship between T2DM and OA at the transcriptional level remains empty. We downloaded OA- and T2DM-related bulk RNA-sequencing and single-cell RNA sequencing data from the Gene Expression Omnibus (GEO) dataset. Differential expression analysis and weighted gene co-expression network analysis (WGCNA) were performed to screen out hub genes between OA and T2DM, and functional enrichment was done. Single-cell sequencing analysis was further used to screen key genes on OA and T2DM datasets. Rat chondrocytes and human articular cartilage were used to validate biomarkers among OA and T2DM. Sixty-eight hub genes were obtained, which were mainly enriched in the inflammatory response. We found that the hub gene TNFAIP6 is not only closely related to OA and T2DM but also a marker of prehypertrophic chondrocytes, which are closely related to the progression of OA. TNFAIP6 was found to be significantly elevated in CD14 + monocytes in T2DM patients, and this group of cells can promote inflammation. Validation on rat chondrocytes and human cartilage showed that TNFAIP6 was highly expressed in OA and further increased in the presence of T2DM or high glucose. Our study identified several characteristic modules and hub genes in the pathogenesis of T2DM-induced OA, which may facilitate further investigation of its molecular mechanisms. Up-regulated TNFAIP6 may contribute to OA in patients with T2DM by the recruitment of pro-inflammatory CD14 + monocytes in the OA synovium, which provides a potential target for the diagnosis and treatment of T2DM-associated OA.